2023
DOI: 10.3390/polym15102349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glue Spread on Bonding Strength, Delamination, and Wood Failure of Jabon Wood-Based Cross-Laminated Timber Using Cold-Setting Melamine-Based Adhesive

Yusup Amin,
Renaldi Purnomo Adji,
Muhammad Adly Rahandi Lubis
et al.

Abstract: Cross-laminated timber (CLT) has become a popular engineered wood product due to its innovative properties and rapid development, which involves the use of various wood species and adhesives. This study aimed to assess the effect of glue application on the bonding strength, delamination, and wood failure of CLT made from jabon wood and bonded with a cold-setting melamine-based adhesive at three different rates: 250, 280, and 300 g/m2. The adhesive was composed of melamine–formaldehyde (MF) by adding 5% citric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The resulting mixture was then manually stirred for 1-2 min at 27 ± 2 • C, yielding a cold-setting melamine-based adhesive. According to a previously published study, the fundamental properties of the adhesives used in this study are shown in Table 1 [1]. The evaluation of wettability was performed through the measurement of the dynamic contact angle between the MF-based adhesives and the surface of Jabon wood.…”
Section: Contact Angle Measurementmentioning
confidence: 99%
See 4 more Smart Citations
“…The resulting mixture was then manually stirred for 1-2 min at 27 ± 2 • C, yielding a cold-setting melamine-based adhesive. According to a previously published study, the fundamental properties of the adhesives used in this study are shown in Table 1 [1]. The evaluation of wettability was performed through the measurement of the dynamic contact angle between the MF-based adhesives and the surface of Jabon wood.…”
Section: Contact Angle Measurementmentioning
confidence: 99%
“…The viscosity difference between the MF-0 and MF-I adhesives also exhibits an effect, alongside the initial contact angle and contact angle reduction ratio. The higher viscosity of MF-1 compared to MF-0 [1] hinders the absorption of the adhesive into the wood surface, resulting in a longer time required to reach the equilibrium contact angle. comparison to MF-0 (Table 1).…”
Section: Contact Angle and Dynamic Wettabilitymentioning
confidence: 99%
See 3 more Smart Citations